Controlling Organic Room Temperature Phosphorescence through External Heavy‐Atom Effect for White Light Emission and Luminescence Printing. Issue 4 (18th December 2019) - She, Pengfei; Yu, Yaxin; Qin, Yanyan; Zhang, Yingjie; Li, Feiyang; Ma, Yun; Liu, Shujuan; Huang, Wei; Zhao, Qiang
Abstract: Pure organic materials with tunable room temperature phosphorescence (RTP) have attracted considerable interest because they are promising candidates for a wide range of optoelectronic applications. Herein, a series of organic compounds of (4‐(9H‐carbazol‐9‐yl)butyl) triphenylphosphonium (CBTP) with different halide anions (CBTP‐Cl, CBTP‐Br, and CBTP‐I) are synthesized. They show emission color changes from blue to orange‐red in the solid state. Single‐crystal X‐ray diffraction analysis and theoretical calculations demonstrate that the RTP is primarily caused by the external heavy‐atom effect (EHE), which enhances the spin–orbit coupling between the singlet and triplet excited states to facilitate the intersystem crossing rate. Distinct white light emission can be achieved using the controllable RTP by doping a certain ratio of potassium iodide (KI) into a polymer matrix containing CBTP‐Cl. Moreover, luminescent information can be recorded on a paper substrate made from a polymer film containing CBTP‐Cl with KI aqueous solution as the ink. The results suggest that rational control of the EHE of these pure organic materials is promising for different optoelectronic applications, including solid‐state lighting, data recording, and security protection. Abstract : Organic molecules with different halide anions (CBTP‐Cl, CBTPBr, CBTP‐I) are synthesized, which show different emission colors in the solid state. Distinct white light emission can be achieved by doping I − into a polymer matrix containing CBTP‐Cl. Moreover, luminescent information can be recorded on a paper substrate made from a polymer film containing CBTP‐Cl with KI aqueous solution as the ink.